2021
DOI: 10.1093/cercor/bhab020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ultrastructural Analysis of Thalamocortical Innervation of the Primary Motor Cortex and Supplementary Motor Area in Control and MPTP-Treated Parkinsonian Monkeys

Abstract: The synaptic organization of thalamic inputs to motor cortices remains poorly understood in primates. Thus, we compared the regional and synaptic connections of vGluT2-positive thalamocortical glutamatergic terminals in the supplementary motor area (SMA) and the primary motor cortex (M1) between control and MPTP-treated parkinsonian monkeys. In controls, vGluT2-containing fibers and terminal-like profiles invaded layer II–III and Vb of M1 and SMA. A significant reduction of vGluT2 labeling was found in layer V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 189 publications
4
10
0
Order By: Relevance
“…For example, recent studies highlighted a critical role of indirect pathway striatal projection neurons in driving cellular and synaptic adaptations in basal ganglia nuclei in parkinsonism, such as the subthalamic nucleus (Chu et al, 2017;Sharott et al, 2017;Ryan et al, 2018;McIver et al, 2019). Similarly, pathologic basal ganglia outputs in parkinsonism can drive adaptive changes in M1 via the thalamocortical projections (Villalba et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies highlighted a critical role of indirect pathway striatal projection neurons in driving cellular and synaptic adaptations in basal ganglia nuclei in parkinsonism, such as the subthalamic nucleus (Chu et al, 2017;Sharott et al, 2017;Ryan et al, 2018;McIver et al, 2019). Similarly, pathologic basal ganglia outputs in parkinsonism can drive adaptive changes in M1 via the thalamocortical projections (Villalba et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The density of vGluT2-ir puncta was significantly decreased in slices from 6-OHDA mice relative to those from controls (control = 20.4 [16.9–22.9] million puncta/mm 3 , n = 20 slices/3 mice; 6-OHDA = 11.2 [8.5–13.9] million puncta/mm 3 , n = 20 slices/3 mice; p < 0.0001, MWU; Figure 3A-C ). These data are consisted with findings from MPTP-treated NHP (Villalba et al, 2021). It has been reported that reduced vGluTs levels per terminal leads to a smaller vesicle size (Wojcik et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Thalamic axon terminals target the dendritic spines and dendritic shaft of M1 PT neurons (Hooks et al, 2013;Kuramoto et al, 2009;Villalba et al, 2021). To interrogate postsynaptic structural changes associated with DA degeneration, the density of dendritic spines and the diameter of dendritic shaft of M1 PT neurons were assessed in slices from controls and 6-OHDA mice that received AAVrg-hSyn-eGFP injections into the pontine nuclei (Figure 3D, E).…”
Section: Loss Of Da Alters the Structure Of Thalamocortical Synapses ...mentioning
confidence: 99%
See 2 more Smart Citations